Effect of using Cordia myxa Crude Extract Creams in Wounds and Burns Treatments - Aliaa S. Al-Faraji (Journal of Global Pharma Technology, 2019)
It was found that the use of Bumper extract cream (Cordia myxa) has a high effect on the healing of wounds and burns in the experimental mice. All rat assemblies and experiments are designed according to the standard procedures. The creams were applied on laboratory mice (Swiss albino mice), which is located in the laboratories of the Center for the Preparation of Medicines / Ministry of Industry and graduated doses (1 and 2% w / w) and apply these creams to wounds and burns induced laboratory / for 10 days of treatment daily. A group of mice was designed also wounds and burns were stimulated, but treated with  Ficidin@ and Flamazin@ ointment were used as standard (2% w/w) for treatment of wound and burn respectively. The results of the study showed the effectiveness of the bumper extract with high concentration of 1% and 2% on the healing of wounds and burns compared to control and standard groups. The results of the textile cutting showed the effectiveness of the pampers on the formation of the granular tissue for burns and wounds, which in turn leads to the rapid recovery of these wounds and burns within 10 days. Results investigated the highest effectiveness of bumper extracts on the rapid recovery of wounds and burns in rats faster than using chemical medication, and thus support its traditional use.Keywords: Ficidin- Flamazin -Cordia myxa cream-Excision Wound & Burn-Healing.